PENGARUH MEDIA CROSSWORD PUZZLE TERHADAP HASIL BELAJAR SISWA PADA MATERI SISTEM PERNAFASAN - Lamondo, Djuna; Sabrina Mohamad, Sitti; Dama, Lilan; Solang, Margaretha; Mardin, Herinda; Nur Akbar, Muh. (Jurnal Biogenerasi, 2024)
This study is an experimental study aimed at determining the use of crossword puzzle media in enhancing student learning outcomes in the learning material of the human respiratory system for class XI IPA 3 students at SMA Negeri 4 Kota Gorontalo. This study employed a descriptive statistical quantitative method using a one-group design pre-test and post-test. The population consisted of class XI IPA 3 students at SMA Negeri 4 Kota Gorontalo, totaling 30 students. Data collection techniques included interview and tests. The findings are as follows: based on the data analysis, it is evident thet there is an enhancement in student learning outcomes for class XI IPA 3 students at SMA Negeri 4 Kota Gorontalo. Furtheremore, based on the descriptive study, it indicates that the average student learning outcomes before the use of crossword puzzles media. Moreover, based on statistical analysis of student learning outcomes, it obtains a t-count value of 0,027 with a significant level of 0,05, hence 0,027 > 0,05. This shows that there is a significant difference between student learning aoutcomes before and after the use of crossword puzzle media in class XI IPA 3 at SMA Negeri 4 Kota Gorontalo.